Biokonversi Sampah Organik Berbasis Maggot BSF dalam Pemberdayaan PKK RT 1 RW 7 di Kelurahan Sumbersari, Jember: Bioconversion of Organic Waste Using BSF Maggots in the Empowerment of PKK RT 1 RW 7 in Sumbersari Subdistrict, Jember - Habriantono, Bakhroini; Irsyadi, Muhammad Burhanuddin; Suharto, Suharto; Wagiyana, Wagiyana; Alfarisy, Fariz Kustiawan; Nurlaelita, Khaerani; Dewi, Rifani Rusiana; Sari, Wahyu Intan; Latifa, Siti Nur; Ramadhan, Gilang; Fourthina, Amanda Intan; Setyawan, Rizki Agus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Household organic waste is a major component of waste generation in densely populated residential areas, especially in urban areas with limited land and time. In RT 1 RW 7, Sumbersari Village, waste management is not optimally carried out, as the waste transportation system still relies on the door-to-door method, with no processing at the household level. This community service program aims to increase community awareness and involvement, especially among PKK mothers, in managing organic waste through bioconversion technology using Black Soldier Fly (BSF) maggots. The activity was carried out through a participatory approach in the form of a Focus Group Discussion (FGD) that was aligned with the PKK's regular meeting agenda. Residents were educated on how to use maggots, starting with sorting organic and non-organic waste. PKK mothers were also shown the decomposition process using BSF maggots firsthand, thereby convincing them of the program's benefits. Regular monitoring and evaluation were conducted to assess the program's effectiveness and changes in community behavior in sorting and processing waste. Monitoring results showed that most residents were quite enthusiastic about implementing the organic waste conversion program with maggots.